Mantenimiento preventivo y correctivo de mecánica automotriz y su incidencia en la generación de recursos económicos en jóvenes de la parroquia Barreiro Nuevo del cantón Babahoyo, provincia de los Ríos - Cordova Chalan, Nelson Hernán (2017)
The final report of the research work contains very important aspects to strengthen the development of the autonomy of the youth of Barreiro New Babahoyo canton Los Ríos province, through the system of preventive and corrective maintenance, in which resources were generated economic, taking it as the best results of the autonomous work of the Youth and his companions; taking advantage of this way the best aptitude and what they like to do the most. This investigative work called, Preventive and corrective maintenance of automotive mechanics and its incidence in the generation of economic resources in young people of the Barreiro Nuevo parish of the Babahoyo county, Los Ríos province, that after detecting the problem that was presented in the Youth, we formulate clear objectives, both general and specific, precise measurable and achievable, implementing strategies to advance at the pace of the scientific and technological social demands that many times achieve their expectations, while others could not escape the stagnation and delay for the good of the same and of those who participate as students of this center of knowledge we can meet our goals and objectives. To obtain this final report, we went through a process, which is based on a theoretical framework and a statistical analysis that helped us to identify the major problems and then give them possible solutions through a proposal called "Safety Manual to facilitate learning Of the youngs"; on the basis of bibliographic means that will allow reaching the expected results for the benefit of this most vulnerable sector of society